W2, p-Solvability of the Dirichlet Problem for Elliptic Equations with Singular Data. (19th January 2015) - Caso, Loredana; D'Ambrosio, Roberta; Transirico, Maria
Abstract : We give an overview on some results concerning the unique solvability of the Dirichlet problem inW 2, p, p > 1, for second-order linear elliptic partial differential equations in nondivergence form and with singular data in weighted Sobolev spaces. We also extend such results to the planar case.